A survey of robotic caging and its applications. (18th October 2017) - Makita, Satoshi; Wan, Weiwei
Abstract: This paper presents a brief survey of robotic caging and its applications. Caging is a kind of grasping methods, which can be accomplished geometrically by position-controlled robotic agents, and has advantages over conventional manipulation which requires to fulfill mechanical conditions. Due to the advantages, caging was extensively studied and applied in robotics. This paper reviews the robotic literature related to caging ranging from its historical background, state-of-the-art developments, to practical applications. It provides our insights on some open problems and promising research and application directions. We hope the paper could help researchers quickly catch the strength and limitations of caging, and make impacting contributions to the research community. Graphical Abstract: